Teachers’ Speech Style in Teaching English - Sherliane Trisye Poai (Sintuwu Maroso Journal of English Teaching, 2017)
This research is aimed to find out English teacher speech style toward at SMA Negeri 1 Poso. The subjects of this research are two English teacher at SMA Negeri 1 Poso. Design of this research was descriptive qualitative. The instrument of this research are observation, recorder, questionnaires and documentation. Data were gained by the result of the recorder is transcript and questionnaires. The finding obtained that the dominant speech style that the teachers used are casual speech style, informal speech style, formal speech style, consultative speech style and serious speech style. The learning process is going well and the students give a good response in learning. Based on the result of the research it can be concluded that the dominant speech style used by the English teachers are casual speech style, informal speech style, formal speech style, consultative speech style andserious speech style.Keywords: speech style, teaching English